Preparation method of flame-retardant, washable and moderate-compatibility water-based acrylate resin coating key material
By introducing carbon-forming agent intermediates, DOPO and 3,4-epoxy-1-butene into aqueous acrylate resin coatings, combining hydrophilic acrylamide and hydroxyethyl acrylate, the problem of poor heat resistance of the washable coatings during drilling of PCB boards is solved, and efficient cleaning of the coating film and improved the performance of the circuit board.
Patent Information
- Application Number
- CN202411755149.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing washable coatings are melted due to poor heat resistance during the drilling process of PCB board, which affects the drilling accuracy, and the coating remains difficult to clean, affecting the performance and life of the circuit board.
The flame-retardant, washable and moderate compatibility of aqueous acrylate resin coating is used to conduct radical reactions by introducing carbon-forming agent intermediates, DOPO and 3,4-epoxy-1-butene into the core layer to improve the flame retardancy and heat resistance of the coating, and hydrophilic acrylamide and hydroxyethyl acrylate into the shell layer to enhance the water-retardancy.
It improves the flame retardancy and heat resistance of the coating, ensures that the coating does not melt during the drilling process, reduces the amount of coating residues in the holes of the PCB board, simplifies the cleaning process, and improves the service performance and life of the circuit board.
Smart Images

Figure BDA0005166082090000131 
Figure BDA0005166082090000141 
Figure BDA0005166082090000142
Abstract
Description
[0001] The present invention is a divisional application of 2024114197324. Technical Field
[0002] The invention relates to a method for preparing a water-based acrylic resin coating, in particular to a method for preparing a flame-retardant, water-washable and moderately compatible water-based acrylic resin coating. Background Art
[0003] Temporary protective coatings are similar to general protective coatings, and can protect and remove dirt on the surface of the protected object. The difference is that the former has a short action time and mainly plays a protective role during processing, transportation or temporary storage. After the processing, transportation and storage process, the coating layer needs to be removed from the surface of the protected object. After the coating is removed, the original functions and properties of the protected object cannot be damaged or negatively affected. This kind of coating that plays a temporary protective role is also called removable coating or washable coating. Washable coatings can form a tightly structured film layer after being applied to the protected object, which can isolate the protected material from the outside world. At the same time, surface adsorption, adhesion and other effects during the film formation process can absorb dirt on the protected object.
[0004] Washable coatings are often removed from the surface of the protected object by soaking or washing with a specific solvent. The film must have a certain solubility in the solvent, which includes water, acid and alkali liquids, or specially formulated paint strippers. It is mainly used for glass and metal surface protection, or for vacuuming walls and floors and purifying the air.
[0005] PCB circuit boards are the cornerstone of electronic components. During the manufacturing process of PCB circuit boards, drilling accuracy is one of the core indicators to measure PCB quality. Removable coatings are the key to industrial transformation and upgrading, and washable coatings are the key to affecting PCB drilling accuracy. Applying removable coatings on aluminum plates, and then attaching the aluminum plates with removable coatings to circuit boards (copper substrates, copper clad boards), and then drilling can improve the drilling accuracy of circuit boards. Coatings are consumables, and after the drilling operation is completed, the PCB needs to be cleaned to remove the coating film. The water-washable coatings used in PCB processing on the market today generally have the following pain points: (a) PCB drilling requires drilling with the aluminum plate coating, but traditional water-washable coatings have poor heat resistance and cannot withstand the heat released during drilling operations, causing the coating film to partially or completely melt, affecting drilling accuracy; (b) Paint splashed during drilling is easy to adhere to the epoxy resin through-holes of the PCB and is difficult to handle. Residual paint is easy to cause moisture, mold, and corrosion of the circuit board, affecting the performance and life of the circuit board; (c) The resin adhesion between the PCB and the aluminum plate is not moderate, with poor adhesion, poor compatibility with the metal (aluminum plate), and difficulty in protection. The adhesion is too strong and it is also difficult to clean.
[0006] Jia Danfeng et al. prepared water-soluble acrylic resin by solution free radical polymerization method, using acrylic acid (AA), hydroxyethyl methacrylate (HEMA), acrylamide (AM) as functional monomers, butyl acrylate and methyl methacrylate as soft and hard monomers, azobisisobutyronitrile (AIBN) as initiator, and dimethylethanolamine as neutralizer. Then the water-soluble acrylic resin was compounded with the emulsion to prepare a water-based compounded resin for resin coating. The water-based compounded resin was compounded with fillers, water-soluble polymers and other additives to prepare a water-washable temporary protective coating. It was found that the adhesion of the film was level 2, and the demolding time at 50°C was 50s, showing a good water washing time. However, this technology did not consider the problem of temporary coating film bonding with metal materials when heated during use, which caused the film to melt and be difficult to clean, and did not study core indicators such as PCB drilling accuracy.
[0007] Invention patent CN202210702763.5 involves using polyvinyl alcohol (PVA) resin as the main resin to improve the flexibility of the paint film; using polyether-modified acrylic resin as the modified resin to improve the adhesion of the paint on soft PVC and improve the water solubility of the PVA resin. At the same time, a small amount of acrylic-modified polyurethane (PUA) resin is used as the second modified resin to improve the bonding strength with soft PVC and resist cracking caused by deformation of the material. The invention also adds carboxylic acid-type propyl beet amphoteric surfactants to the coating, which has the dual effects of thickening and improving water washing residues, thereby accelerating the dissolution rate of the paint film when washed with water. Therefore, the coating provided by the invention has excellent flexibility, is not easy to crack, and has a good water washing effect. However, the patent involves cleaning of soft PVC, which is different from the use environment of the coatings used for aluminum plates and PCB epoxy resin boards, and does not involve the standard requirements for flame retardancy of acrylic esters.
[0008] Invention patent CN2015105882116 A kind of anti-carburizing coating that can be washed and removed after quenching is prepared by the following mass percentage components: 25-35% boric acid, 15-25% filler, 15-25% aluminum dihydrogen phosphate, 1-5% coloring pigment and 30-40% water. The invention also discloses a preparation method of the above anti-carburizing coating that can be washed and removed after quenching. The anti-carburizing coating can be removed by washing after carburizing heat treatment, thereby solving the problem that traditional anti-carburizing coating is difficult to peel off after carburizing heat treatment. Inorganic high temperature resistant materials are used as anti-carburizing agents in the formula of anti-carburizing coating. The anti-carburizing coating formed after the anti-carburizing agent is brushed on the surface of the workpiece has good adhesion, and does not peel or flow at high temperature, and does not affect the carburizing atmosphere. The invention does not involve a film-forming agent with polyurethane resin as a film.
[0009] Invention patent 201910576686.1 relates to a glue-coated aluminum-based cover plate for PCB drilling and its preparation method, wherein the water-soluble composite polymer resin layer has moderate toughness and can play a guiding role during the falling process of the drill needle, thereby improving the drilling accuracy; at the same time, the hot-melt resin in the water-soluble composite polymer resin layer can lubricate the drill bit and cool the drill needle during drilling, thereby effectively improving the roughness of the hole wall, reducing wire winding, lowering the drill bit temperature, and extending the service life of the drill needle; in addition, the water-soluble composite polymer resin layer has good water solubility, is easy to handle after drilling, and is not easy to adhere to the holes in the PCB, thereby ensuring the drilling quality. The disadvantage of this resin is that it does not study whether the glue attached to the PCB hole during drilling can be cleaned, and does not emphasize the bonding of the film generated by the drill bit when heated.
[0010] Invention patent 201310504176.6 involves the following steps: (1) pre-processing the circuit board substrate, drilling through holes and copper deposition, board surface electroplating, outer layer circuit pattern transfer, pattern electroplating, etc.; 2) back drilling on PCB board 4 to detect whether the back drilling hole depth is qualified; 3) alkaline etching and photosensitive solder mask are performed on the drilled back drilling hole to finally obtain the finished product. The key points of its technical solution are: when back drilling, the drill belt coefficient used in the drilling through hole process should be modified according to the expansion and contraction data that appears in the process from drilling through holes to drilling back holes on PCB board 4, so as to keep the drill belt data consistent with the actual expansion and contraction; the drilling surface in the drilling through hole process is consistent with the drilling surface during back drilling; a layer of phenolic pad 6 is added on the top of PCB board 4; the depth accuracy and position accuracy of the existing back drilling holes on PCB board 4 can be effectively improved to ensure the integrity of the signal transmission on PCB board 4. The invention does not study the cleaning of the coating film and the bonding of the drill film and the adhesion of fragments.
[0011] In summary, the prior art has not comprehensively studied the burning droplets of water-washable coatings applied in the aluminum cover, the heat tolerance (pkHHR, THR), the water washability of the film on the aluminum cover, the hole position accuracy of the PCB core, the hole wall roughness and the drill temperature, and the aperture melt and other indicators. The above indicators are the key to evaluating the performance of water-washable coatings, so research is imperative. Summary of the invention
[0012] The purpose of the present invention is to solve the problem that when drilling holes in the coating of a PCB board, the coating melts, which affects the drilling accuracy. At the same time, the coating melts due to heat, resulting in mucus of the film adhering to the hole of the PCB board, which solidifies and is difficult to remove. In view of the existing drawbacks, the present invention designs a flame-retardant, washable and moderately compatible water-based acrylic resin coating. First, in view of the thermal melting, the flame retardancy is improved to improve its index. A carbonizing agent intermediate is used in the core layer to react with DOPO and 3,4-epoxy-1-butene for free radical reaction, and the above substances are introduced into In the acrylic ester monomer chain segment, since both DOPO and p-hydroxybenzaldehyde have benzene ring rigid groups, their surface strength during the drilling process is moderate, and the accuracy will not be reduced due to high-speed movement during the drilling process, and the resin film will not be broken to form too many small particles and splash onto the PCB board, thereby reducing the number of resin film particles on the PCB board; secondly, the addition of 3,4-epoxy-1-butene will not make the resin film formed by DOPO and p-hydroxybenzaldehyde too hard and cause it to crack; using porous carbon layer modification , DOPO and 3,4-epoxy-1-butene participate in the shell free radical reaction, and the above substances are introduced into the acrylic resin segment to reduce the flammability of the acrylic resin; at the same time, the gelatinized starch also enhances the melting resistance of the PCB; then some hydroxyl groups of the soluble starch are used to react with the acyl chloride of benzoyl chloride to prevent the viscosity from increasing too much in the subsequent gelatinization; ammonium persulfate is used as an initiator to react acrylamide, hexadecyl dimethyl allyl ammonium chloride and N,N-methylenebisacrylamide with free radicals The solution reacts to form a soluble acrylic resin, and then the starch gelatinization is accelerated in an alkaline environment. The resulting gelatinized soluble starch has three functions: a. increasing the melting temperature of the acrylic resin, b. improving the water solubility of the acrylic resin, and c. increasing the swelling of the acrylic resin when heated and washed with water, so that it can be quickly peeled off from the epoxy resin PCB board and achieve moderate compatibility with the PCB board; in order to solve the water problem, hydrophilic acrylamide and hydroxyethyl acrylate are introduced into the shell layer to increase the water washability of the shell layer.
[0013] The preparation method of the flame-retardant, water-washable, moderately compatible water-based acrylic resin coating is prepared according to the following steps:
[0014] (1) Preparation of core layer emulsion: Add 600-800 g of water, 11-17 g of emulsifier A, and 24-41 g of methacrylic acid into a reaction container, mix and stir evenly, heat to 40-45° C., stir and react for 60 min, add monomer A, 10.2-13.4 g of carbonizing agent intermediate, 18.3-21.6 g of DOPO, and 2.1-6.3 g of 3,4-epoxy-1-butene, and emulsify for 20-30 min; heat to 65° C., pass reflux water, heat to 80-90° C., dropwise add 10-12 g of initiator, dropwise add for 1-1.5 h, react for 1-2 h, then add 3.15-8.4 g of diethanolamine, adjust the pH to 8, and react at 80-90° C. for 1-2 h to obtain core layer emulsion;
[0015] (2) To the entire core layer emulsion obtained in step (1), all monomers B and 8-12 g of initiator are simultaneously added dropwise for 1 h, and the mixture is stirred at 75-85° C. for 1.5 h, and then 4.6-5.5 g of porous carbon layer modifier, 4.1-4.3 g of DOPO and 1.2-2.4 g of 3,4-epoxy-1-butene, 2.1 g of initiator and 1.1-2.3 g of starch modifier are added, and the mixture is reacted at 60-70° C. for 1 h, and the mixture is cooled to 50° C., and 14-20 g of emulsifier B is added, and the reaction time is 30 min. Ammonia water is added to adjust the pH value to 7-8, and the flame-retardant, washable, and moderately compatible water-based acrylic resin coating is obtained;
[0016] The monomer A is prepared by mixing 40-55g of ethyl acrylate, 28-48g of methyl methacrylate and 38-52g of hydroxyethyl acrylate;
[0017] The monomer B is prepared by mixing 49-69 g of acrylamide, 12-54 g of methyl methacrylate and 55-92 g of hydroxyethyl acrylate.
[0018] The emulsifier A is prepared by mixing sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2:1;
[0019] The preparation method of the carbon-forming agent intermediate is as follows:
[0020] Add 6.1g of p-hydroxybenzaldehyde into a beaker, stir and dissolve with 100-150mL of ethanol, pour into a 250mL three-necked flask, stir at a speed of 250r / min, heat to 50-60°C, slowly drop 1.5-1.8g of ethylenediamine diluted with 10mL of ethanol into the three-necked flask through a constant pressure dropping funnel, add dropwise for 30min, continue the reaction for 1-2.5h, stop heating, cool to room temperature, filter and obtain a light yellow crude carbon-forming intermediate, wash with ethanol three times, and vacuum dry at 60°C for 18-24h to obtain a light yellow carbon-forming intermediate powder, which is a carbon-forming agent intermediate.
[0021] The initiator is any one of ammonium persulfate and potassium persulfate;
[0022] The preparation method of the porous carbon layer modified material is as follows:
[0023] (1) Cut the vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, heat them at 400° C. for 3 to 4 hours in a nitrogen atmosphere for pre-carbonization, mix the obtained carbonized product with KOH in a mass ratio of 1:3, then add 300% of its weight of water to the mixture, and stir at 40 to 50° C. for 18 to 22 hours, then dry the product, and again carbonize and keep warm at 500 to 600° C. for 1 to 2 hours under nitrogen protection, and finally dry it to obtain a porous carbon layer;
[0024] (2) 0.5 g of a porous carbon layer, 4.5-6.7 g of pyrrole, 100 mL of water, and 0.4-0.6 g of sodium p-toluenesulfonate were stirred at 50-60° C. for 2-4 h, the product was dried, and then 50 mL of DMF and 8.17-11.2 g of erythritol were added, the pH was adjusted to 7.5, and the mixture was stirred and reacted at 50-70° C. for 1-2 h. Then 27.4-36.4 g of phosphorus trichloride was added, and the mixture was reacted at 30-40° C. for 1-2 h. Then 12.5-15.3 g of myristic acid was added, and the mixture was reacted at 30-45° C. for 1-2 h. The product was dried to obtain a porous carbon layer modified product.
[0025] The preparation method of the starch modified material is as follows: add 1-1.2g of benzoyl chloride and 15mL of benzene to 4g of soluble starch, stir and react at 30-40°C for 30-40min, rotary evaporate at 40-50°C, and dry to obtain a starch reactant; then add 20mL of 70°C deionized water to the starch reactant, stir for 30-40min, add 0.03-0.05g of ammonium persulfate at 50-60°C to obtain a pregelatinized soluble starch solution; then add 5.8g of acrylamide, 2.3g of hexadecyl dimethyl allyl ammonium chloride and 2g The mixture is mixed with N,N-methylenebisacrylamide, added into 10mL deionized water to dissolve, then the solution is slowly poured into the pre-gelatinized soluble starch solution, the pH of the soluble starch solution is adjusted to 7.0 with 1mol / L NaOH aqueous solution, reacted for 15-30min, the mixed solution becomes a gel state, stirred at 60-70℃ for 2-3h, then the gel is cut into pieces with scissors, placed in an electric blast drying oven at 90℃ for reaction for 2-3h, finally taken out and dried for 24h, crushed and passed through an 18-mesh sieve to obtain a starch modification;
[0026] The emulsifier B is AEO-9.
[0027] The positive effects of the present invention are:
[0028] (1) The present invention constructs a core-shell flame-retardant, washable and moderately compatible water-based acrylic resin. The core layer uses a relatively hard segment and the shell layer uses a soft segment. At a relatively high temperature, the film can quickly fall off from the hole of the PCB board during cleaning; the core layer uses a carbon-forming agent intermediate and DOPO and 3,4-epoxy-1-butene to react with free radicals, and the above substances are introduced into the acrylic monomer segment. Since DOPO and p-hydroxybenzaldehyde both have a benzene ring rigid group, the accuracy will not be reduced due to the high-speed movement during the drilling process, and the resin film will not be interrupted to form too many small particles that splash onto the PCB board, thereby reducing the PCB The number of resin film particles on the board; secondly, the addition of 3,4-epoxy-1-butene will not make the resin film formed by DOPO and p-hydroxybenzaldehyde too hard and cause it to crack, and at a pH of 8, 3,4-epoxy-1-butene is ring-opened, and diethanolamine with strong hydrophilicity is introduced. The -NH of diethanolamine is used to open the ring with epoxy in an alkaline environment. On the one hand, nitrogen-containing elements with flame retardant effects are introduced into the acrylic resin chain. On the other hand, the introduced hydroxyl groups not only enhance the hydrophilicity of the resin core layer, but also dehydrate the hydroxyl groups into carbon during the heating process of the resin, thereby enhancing the resistance to droplets of the resin, reducing the resin film particles on the PCB board, and enhancing the water washability;
[0029] (2) The present invention utilizes the aldehyde group of p-hydroxybenzaldehyde and the amino group of ethylenediamine to form a Schiff base through condensation of the aldehyde group and the imino group. This reaction is very easy to occur to generate an imine bond. Then, under the action of an initiator, the carbonizing agent intermediate, DOPO and 3,4-epoxy-1-butene undergo a free radical reaction, wherein the pH of DOPO reacts with the C=N or C=C double bond through an addition reaction to generate a core layer. Ethylenediamine provides nitrogen elements, and generates nitrogen and other flame-retardant gases during the combustion process, causing the carbon layer to expand. p-hydroxybenzaldehyde and DOPO provide carbon sources, and during combustion, a dense carbon layer is formed to cover the surface to isolate heat and oxygen. The phosphorus element in DOPO captures oxygen free radicals released by combustibles, reducing the possibility of combustion, thereby achieving a flame retardant effect.
[0030] (3) The present invention utilizes vegetable tanned leather scraps to be carbonized in a nitrogen atmosphere, isolating them from oxygen, and uses KOH to increase their fluffiness. The carbonization is continued to obtain a porous carbon layer, and pyrrole is dispersed in the porous carbon layer. The phase change material erythritol reacts with the NH bond of pyrrole, and the excess hydroxyl reacts with phosphorus trichloride. The excess phosphorus-chlorine bond reacts with myristic acid having a phase change, so that a large amount of phase change material is introduced into the porous carbon layer. When the material is heated, it can absorb part of the heat and delay the possibility of combustion. At the same time, a large amount of carbon in the porous carbon layer reduces the possibility of combustion. Then, the porous carbon layer modifier, DOPO and 3,4-epoxy-1-butene are used to participate in the shell free radical reaction, and the above substances are introduced into the acrylic resin segment to reduce the flammability of the acrylic resin.
[0031] (4) The present invention utilizes part of the hydroxyl groups of soluble starch to react with the acyl chloride of benzoyl chloride, so that the viscosity of the soluble starch will not be excessively increased during the subsequent gelatinization; then the soluble starch is gelatinized in water, and the hydroxyl groups in the remaining starch are reacted with the amino group or the imino group, and ammonium persulfate or the like is used as an initiator to react acrylamide, hexadecyl dimethyl allyl ammonium chloride and N,N-methylene bisacrylamide in a free radical solution reaction to form a soluble acrylic resin; then the starch gelatinization is accelerated in an alkaline environment. The obtained gelatinized soluble starch has three functions: a) increasing the melting temperature of the acrylic resin; b) improving the water solubility of the acrylic resin; and c) increasing the swelling of the acrylic resin when heated and washed with water, so that the acrylic resin can be quickly peeled off from the epoxy resin PCB board to achieve moderate compatibility with the PCB board. DETAILED DESCRIPTION
[0032] Embodiment 1
[0033] The preparation method of the flame-retardant, water-washable, moderately compatible water-based acrylic resin coating is prepared according to the following steps:
[0034] (1) Preparation of core layer emulsion: add 600 g of water, 11 g of emulsifier A (mixed with sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2:1), and 24 g of methacrylic acid into a reaction container, mix and stir evenly, heat to 40°C, stir and react for 60 min, add monomer A, 10.2 g of carbonizing agent intermediate, 18.3 g of DOPO, and 2.1 g of 3,4-epoxy-1-butene, and emulsify for 20 min; heat to 65°C, pass reflux water, heat to 80°C, drop 10 g of ammonium persulfate initiator (dissolved in 50 g of water), drop for 1 h, react for 1 h, then add 3.15 g of diethanolamine, adjust the pH to 8, and react at 80°C for 1 h to obtain core layer emulsion;
[0035] (2) To the entire core layer emulsion obtained in step (1), all monomers B and 8 g of ammonium persulfate initiator (dissolved in 40 g of water) were simultaneously added dropwise for 1 hour, and the mixture was stirred and reacted at 75° C. for 1.5 hours. Then, 4.6 g of porous carbon layer modifier, 4.1 g of DOPO, 1.2 g of 3,4-epoxy-1-butene, 2.1 g of ammonium persulfate initiator (dissolved in 4 g of water) and 1.1 g of starch modifier were added, and the mixture was reacted at 60° C. for 1 hour. The mixture was cooled to 50° C., 14 g of emulsifier B (AEO-9) was added, and the reaction time was 30 minutes. Ammonia water was added to adjust the pH value to 7-8, and the flame-retardant, washable, and moderately compatible water-based acrylic resin coating was obtained.
[0036] The monomer A is prepared by mixing 40 g of ethyl acrylate, 28 g of methyl methacrylate and 38 g of hydroxyethyl acrylate;
[0037] The monomer B is prepared by mixing 49 g of acrylamide, 12 g of methyl methacrylate and 55 g of hydroxyethyl acrylate.
[0038] The preparation method of the carbon-forming agent intermediate is as follows:
[0039] Add 6.1g of p-hydroxybenzaldehyde to a beaker, stir and dissolve it with 100mL of ethanol, and pour it into a 250mL three-necked flask with a stirring speed of 250r / min. Raise the temperature to 50℃, slowly drop 1.5g of ethylenediamine diluted with 10mL of ethanol into the three-necked flask through a constant pressure dropping funnel, and add the dropping time for 30min. Continue the reaction for 1h, stop heating, cool to room temperature, and filter to obtain a light yellow crude carbon-forming intermediate. Wash with ethanol 3 times, and vacuum dry at 60℃ for 18h to obtain a light yellow carbon-forming intermediate powder, which is a carbon-forming agent intermediate.
[0040] The preparation method of the porous carbon layer modified material is as follows:
[0041] (1) Cut the vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, heat them at 400°C for 3 h for pre-carbonization under a nitrogen atmosphere, mix the obtained carbonized product with KOH in a mass ratio of 1:3, then add 300% water of the sample weight to the above mixture, and stir at 40°C for 18 h, then dry the product, and again carbonize and keep warm at 500°C for 1 h under nitrogen protection, and finally dry it to obtain a porous carbon layer;
[0042] (2) 0.5 g of porous carbon layer, 4.5 g of pyrrole, 100 mL of water, and 0.46 g of sodium p-toluenesulfonate were stirred at 50° C. for 2 h, the product was dried, and then 50 mL of DMF and 8.17 g of erythritol were added, the pH was adjusted to 7.5, and the mixture was stirred and reacted at 50° C. for 1 h. Then 27.4 g of phosphorus trichloride was added and the mixture was reacted at 30° C. for 1 h. Then 12.5 g of myristic acid was added and the mixture was reacted at 30° C. for 1 h. The product was dried to obtain a porous carbon layer modified product.
[0043] The preparation method of the starch modified material is as follows: add 1 g of benzoyl chloride and 15 mL of benzene to 4 g of soluble starch, stir and react at 30 ° C for 30 minutes, rotary evaporate at 40 ° C, and dry to obtain a starch reactant; then add 20 mL of 70 ° C deionized water to the starch reactant, stir for 30 minutes, add 0.03 g of ammonium persulfate at 50 ° C to obtain a pregelatinized soluble starch solution; then add 5.8 g of acrylamide, 2.3 g of hexadecyl dimethyl allyl ammonium chloride and 2 g of N, N-methylene The mixture was mixed with bisacrylamide and added into 10 mL of deionized water to dissolve. The solution was then slowly poured into the pregelatinized soluble starch solution. The pH of the soluble starch solution was adjusted to 7.0 with 1 mol / L NaOH aqueous solution. The mixture was reacted for 15 min until the mixed solution became a gel state. The mixture was stirred at 60 ° C for 2 h. The gel was then cut into pieces with scissors and placed in an electric blast drying oven at 90 ° C for reaction for 2 h. The gel was finally taken out and dried for 24 h. The starch was crushed and passed through an 18-mesh sieve to obtain a starch modification.
[0044] Embodiment 2
[0045] The preparation method of the flame-retardant, water-washable, moderately compatible water-based acrylic resin coating is prepared according to the following steps:
[0046] (1) Preparation of core layer emulsion: 800 g of water, 17 g of emulsifier A (mixed with sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2:1), and 41 g of methacrylic acid were added to a reaction container, mixed and stirred evenly, heated to 45°C, stirred and reacted for 60 min, and monomer A, 13.4 g of carbonizing agent intermediate, 21.6 g of DOPO, and 6.3 g of 3,4-epoxy-1-butene were added, and the emulsification time was 30 min; the temperature was raised to 65°C and refluxed water was passed, and the temperature was raised to 90°C, and 12 g of potassium persulfate initiator (dissolved in 30 g of water) was added dropwise, the addition time was 1.5 h, and the reaction was carried out for 2 h, and then 8.4 g of diethanolamine was added, and the pH was adjusted to 8, and the reaction was carried out at 90°C for 2 h to obtain a core layer emulsion;
[0047] (2) To the entire core layer emulsion obtained in step (1), all monomers B and 12 g of potassium persulfate initiator (dissolved in 30 g of water) were simultaneously added dropwise for 1 h, and the mixture was stirred at 85° C. for 1.5 h. Then, 5.5 g of porous carbon layer modifier, 4.3 g of DOPO, 2.4 g of 3,4-epoxy-1-butene, 2.1 g of potassium persulfate initiator (dissolved in 10 g of water) and 2.3 g of starch modifier were added, and the mixture was reacted at 70° C. for 1 h. The mixture was cooled to 50° C., 17 g of emulsifier B (AEO-9) was added, and the reaction time was 30 min. Ammonia water was added to adjust the pH value to 7-8, and the flame-retardant, washable, and moderately compatible water-based acrylic resin coating was obtained.
[0048] The monomer A is prepared by mixing 55g of ethyl acrylate, 48g of methyl methacrylate and 52g of hydroxyethyl acrylate;
[0049] The monomer B is prepared by mixing 69 g of acrylamide, 54 g of methyl methacrylate and 92 g of hydroxyethyl acrylate.
[0050] The preparation method of the carbon-forming agent intermediate is as follows:
[0051] Add 6.1g of p-hydroxybenzaldehyde into a beaker, stir and dissolve with 150mL of ethanol, pour into a 250mL three-necked flask, stir at a speed of 250r / min, heat to 60°C, slowly drop 1.8g of ethylenediamine diluted with 10mL of ethanol into the three-necked flask through a constant pressure dropping funnel, add dropwise for 30min, continue the reaction for 2.5h, stop heating, cool to room temperature, filter and obtain a light yellow crude carbon-forming intermediate, wash with ethanol three times, and vacuum dry at 60°C for 24h to obtain a light yellow carbon-forming intermediate powder, which is a carbon-forming agent intermediate.
[0052] The preparation method of the porous carbon layer modified material is as follows:
[0053] (1) Cut the vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, heat them at 400°C for 4 hours under a nitrogen atmosphere for pre-carbonization, mix the obtained carbonized product with KOH in a mass ratio of 1:3, then add 300% of its weight of water to the mixture, and stir at 50°C for 22 hours, then dry the product, and again carbonize and keep warm at 600°C for 2 hours under nitrogen protection, and finally dry it to obtain a porous carbon layer;
[0054] (2) 0.5 g of porous carbon layer, 6.7 g of pyrrole, 100 mL of water, and 0.6 g of sodium p-toluenesulfonate were stirred at 60 ° C for 4 h, the product was dried, and then 50 mL of DMF and 11.2 g of erythritol were added, the pH was adjusted to 7.5, and the reaction was stirred at 70 ° C for 2 h. Then 36.4 g of phosphorus trichloride was added and the reaction was carried out at 40 ° C for 2 h. Then 15.3 g of myristic acid was added and the reaction was carried out at 45 ° C for 2 h. The obtained product was dried to obtain a porous carbon layer modified product.
[0055] The preparation method of the starch modified material is as follows: add 1.2 g of benzoyl chloride and 15 mL of benzene to 4 g of soluble starch, stir and react at 40 ° C for 40 minutes, rotary evaporate at 50 ° C, and dry to obtain a starch reactant; then add 20 mL of 70 ° C deionized water to the starch reactant, stir for 40 minutes, add 0.05 g of ammonium persulfate at 60 ° C to obtain a pregelatinized soluble starch solution; at the same time, add 5.8 g of acrylamide, 2.3 g of hexadecyl dimethyl allyl ammonium chloride and 2 g of N,N- Mix the methylenebisacrylamide and add it into 10mL deionized water to dissolve. Then slowly pour the solution into the pregelatinized soluble starch solution, adjust the pH of the soluble starch solution to 7.0 with 1mol / L NaOH aqueous solution, react for 30min, and the mixed solution becomes a gel state. Stir at 70℃ for 3h, then cut the gel into pieces with scissors, place it in an electric blast drying oven at 90℃ to react for 3h, finally take it out and dry it for 24h, crush it through an 18-mesh sieve to obtain the starch modification.
[0056] Embodiment 3
[0057] The preparation method of the flame-retardant, water-washable, moderately compatible water-based acrylic resin coating is prepared according to the following steps:
[0058] (1) Preparation of core layer emulsion: add 700 g of water, 14 g of emulsifier A (mixed with sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2:1), and 32.5 g of methacrylic acid into a reaction container, mix and stir evenly, heat to 40°C, stir and react for 60 min, add monomer A, 11.8 g of carbonizing agent intermediate, 20 g of DOPO, and 4.2 g of 3,4-epoxy-1-butene, and emulsify for 25 min; heat to 65°C, pass reflux water, heat to 85°C, dropwise add 11 g of ammonium persulfate initiator (dissolved in 30 g of water), dropwise add for 1 h, react for 1.5 h, then add 5.6 g of diethanolamine, adjust the pH to 8, and react at 85°C for 1.5 h to obtain core layer emulsion;
[0059] (2) To the entire core layer emulsion obtained in step (1), all monomers B and 10 g of ammonium persulfate initiator (dissolved in 30 g of water) are simultaneously added dropwise for 1 hour, and the mixture is stirred and reacted at 80° C. for 1.5 hours. Then, 5 g of porous carbon layer modifier, 4.2 g of DOPO and 1.8 g of 3,4-epoxy-1-butene, 2.1 g of ammonium persulfate initiator (dissolved in 6 g of water) and 1.7 g of starch modifier are added, and the mixture is reacted at 65° C. for 1 hour. The mixture is cooled to 50° C., 20 g of AEO-9 emulsifier B is added, and the reaction time is 30 minutes. Ammonia water is added to adjust the pH value to 7-8, and the flame-retardant, washable, and moderately compatible water-based acrylic resin coating is obtained.
[0060] The monomer A is prepared by mixing 47.5 g of ethyl acrylate, 38 g of methyl methacrylate and 45 g of hydroxyethyl acrylate;
[0061] The monomer B is prepared by mixing 59 g of acrylamide, 38 g of methyl methacrylate, and 73.5 g of hydroxyethyl acrylate.
[0062] The preparation method of the carbon-forming agent intermediate is as follows:
[0063] Add 6.1g of p-hydroxybenzaldehyde into a beaker, stir and dissolve with 125mL of ethanol, pour into a 250mL three-necked flask, stir at a speed of 250r / min, heat to 55°C, slowly drop 1.65g of ethylenediamine diluted with 10mL of ethanol into the three-necked flask through a constant pressure dropping funnel, add for 30min, continue the reaction for 1.5h, stop heating, cool to room temperature, filter and obtain a light yellow crude carbon-forming intermediate, wash with ethanol three times, and vacuum dry at 60°C for 21h to obtain a light yellow carbon-forming intermediate powder, which is a carbon-forming agent intermediate.
[0064] The preparation method of the porous carbon layer modified material is as follows:
[0065] (1) Cut the vegetable tanned leather scraps into blocks with a length and width of 1 cm, place them in a vacuum tube furnace, heat them at 400°C for 3.5 hours under a nitrogen atmosphere for pre-carbonization, mix the obtained carbonized product with KOH in a mass ratio of 1:3, then add 300% of water by weight to the mixture, and stir at 40-50°C for 20 hours, then dry the product, and again carbonize and keep warm at 550°C for 1.5 hours under nitrogen protection, and finally dry it to obtain a porous carbon layer;
[0066] (2) 0.5 g of porous carbon layer, 5.6 g of pyrrole, 100 mL of water, and 0.5 g of sodium p-toluenesulfonate were stirred at 55 ° C for 3 h, the product was dried, and then 50 mL of DMF and 9.68 g of erythritol were added, the pH was adjusted to 7.5, and the reaction was stirred at 60 ° C for 1.5 h. Then 31.9 g of phosphorus trichloride was added, and the reaction was carried out at 35 ° C for 1.5 h. Then 13.9 g of myristic acid was added, and the reaction was carried out at 40 ° C for 1.5 h. The obtained product was dried to obtain a porous carbon layer modified product.
[0067] The preparation method of the starch modified material is as follows: add 1.1 g of benzoyl chloride and 15 mL of benzene to 4 g of soluble starch, stir and react at 35 ° C for 35 minutes, rotary evaporate at 45 ° C, and dry to obtain a starch reactant; then add 20 mL of 70 ° C deionized water to the starch reactant, stir for 35 minutes, add 0.04 g of ammonium persulfate at 55 ° C to obtain a pregelatinized soluble starch solution; then add 5.8 g of acrylamide, 2.3 g of hexadecyl dimethyl allyl ammonium chloride and 2 g of N, N-methylenebis(2-nitropropene)diol; acrylamide, add it to 10mL deionized water to dissolve, then slowly pour the solution into the pre-gelatinized soluble starch solution, adjust the pH of the soluble starch solution to 7.0 with 1mol / L NaOH aqueous solution, react for 22.5min, the mixed solution becomes a gel state, stir at 65℃ for 2.5h, then cut the gel into pieces with scissors, place it in an electric hot air drying oven at 90℃ to react for 2.5h, finally take it out and dry it for 24h, crush it through an 18-mesh sieve to obtain a starch modification;
[0068] The prepared acrylic resin coating was poured into a polytetrafluoroethylene mold with a thickness of 3 mm, and a droplet test, cone calorimetry and other tests were performed.
[0069] Droplet test
[0070] (1) Sample preparation: The prepared acrylic resin film was placed in a constant temperature and humidity chamber set at 23°C ± 0.5°C and 50% ± 5% humidity for 48 h, and then taken out and cut into samples of 110 cm × 10 cm × 3 mm. Two sets of samples were prepared, with 5 samples in each set.
[0071] (2) Parameters: Clamp about 5mm from the top so that the sample is vertically downward, place a rosin board at the bottom of the sample, and pad about 0.3g of absorbent cotton on the board, evenly placed on the board. Adjust the gas flow rate to 105±5mL / min so that the flame height reaches 20±1mm. Set the combustion time to 10s.
[0072] (3) Flame recording: After setting the parameters, start the flame ignition. After the 10s ignition, press the afterflame time start button. When the sample combustion is finished and only sparks are left, press the afterflame combustion end button to enter the afterburning time. When the sample is completely extinguished, press the afterburning time end button and record the afterflame time and afterburning time.
[0073] (4) Molten droplet observation: During the combustion process, pay attention to whether the combustion produces molten droplets, and whether the molten droplets dripping onto the absorbent cotton below will cause secondary combustion, and record the observation results.
[0074] The test was carried out according to ASTM E1354-1990 (2004 standard) and the cone calorimeter 2000 of FTT Company of the United Kingdom was used for analysis and determination. The sample was 10cm×10cm, the thickness was 3mm, and the thermal radiation power was 12kW / m 2 , determine the maximum heat release rate pkHHR kW / m 2 、THR total heat release MJ / m 2 .
[0075] Take 28 parts of acrylic resin coatings from Examples 1 to 3, 0.2 parts of carboxymethyl fiber, 4 parts of polyvinyl pyrrolidone PVP-K30, 3 parts of polyvinyl alcohol, 6 parts of polyethylene glycol, and 1.5 parts of polyoxyethylene polypropylene ether, respectively, add them to 35 parts of distilled water in sequence, stir evenly, add 2.5 parts of polypropylene glycol (PPG-400), 0.5 parts of leveling agent, 0.6 parts of silane coupling agent, stir evenly, filter and let stand to defoam, and record it as the application plan.
[0076] The coating solutions of Examples 1 to 3 were sprayed on the epoxy resin circuit board respectively and dried at 70°C.
[0077] 30min, wash with 50℃ warm water solution (temperature controlled at 50℃, KMnO450g / L, potassium manganate 10g / L, amplitude controlled at 20mm / s, sodium hydroxide 1mol / L, and the rest water);
[0078] The water washing test method: Determination of the film removal time of the reference compound liquid coating [1] Xie Dan, Jia Danfeng. About water-washable temporary protective coatings [J]. Aging and Application of Synthetic Materials, 2017, 46(5): 43-50.
[0079] The PCB hole position accuracy is measured by sampling and slicing under a metallographic microscope, and the hole wall roughness is measured by a secondary element device; the hole position accuracy, hole wall roughness, and hole diameter melt are sprayed with an application solution (coating thickness 0.04mm) on an aluminum foil (0.1mm), and then drilled on the lower PCB board.
[0080] The drill bit temperature is measured using a hot red temperature detector;
[0081] The pore size melt is observed by naked eyes, and the results are compared and divided into small, less and more data (if less than 30 holes have melt out of 100 holes, it is defined as small, 31 to 70 holes are less, and 71 to 100 holes are more);
[0082] The adhesion of the compound liquid coating is determined according to GB / T 9286-1998 and ISO 2409:1992. The soft substrate is an epoxy resin board. Use a blade to scratch 100 small squares of 1mm×1mm on the coating sample, and stick them with transparent tape. The degree of damage to the paint film is observed to determine the adhesion level of the paint film. The results are expressed in 0 to 5 levels, with 0 being the worst and 5 being the best. Moderate compatibility is level 2.
[0083] Table 1 Properties of flame-retardant, water-washable, moderately compatible water-based acrylic resin coatings
[0084] index Embodiment 1 Embodiment 2 Embodiment 3 Comparative Example HkDJ 208.3 205.8 201.6 336.7 THR 33.4 31.6 32.8 92.5 Droplet situation No dripping No dripping No dripping No dripping Water washability (50℃,s) 39 36 38 211 Hole position accuracy (mil) 1.6 1.8 1.5 2.6 Hole wall roughness (μm) 7 8 6 24 Drill bit temperature (℃) 75 82 89 102 Pore size melt few few few many Adhesion(grade) 2 2 2 3
[0085] The second embodiment of 202011318656.X is used as a comparative example, and the same amount is substituted under the same conditions. The flame retardancy, water washability and compatibility of the present invention are improved compared with the comparative example. The PCB board aperture melt of the present invention example is less and easy to clean, and the film around the aluminum cover plate is almost not bonded after the drill bit is heated. However, in the comparative document, the film around the aluminum cover plate is bonded after the drill bit is heated, and the PCB board aperture melt is more and difficult to clean.
[0086] The following study was conducted by performing a comparative experiment using Example 2.
[0087] Table 2 Flame retardant, water washable, moderately compatible water-based acrylic resin coating properties
[0088]
[0089]
[0090] As shown in Table 2, the carbonizing agent intermediate not only affects the flame retardancy of the acrylic resin film (pkHHR, THR and molten droplet), but also affects the drilling accuracy and pore roughness (acrylic resin film sprayed on the aluminum cover plate, the drilling accuracy and pore roughness of the PCB and the pore melt) and the drill temperature. As shown in Table 2, the indicators without the addition of the carbonizing agent intermediate are not as good as those with the addition of the above substances.
[0091] Table 3 Effects of porous carbon layer modifiers on flame retardant, water-washable, moderately compatible water-based acrylic resins and their application properties
[0092]
[0093]
[0094] As shown in Table 3, the porous carbon layer modifier, phosphorus trichloride, myristic acid and erythritol can improve the flame retardancy, pore position accuracy and pore wall roughness of acrylic resin.
[0095] Table 4 Effects of starch modifications on flame retardant, water-washable, moderately compatible water-based acrylic resins and their application properties
[0096]
[0097] It can be found from Table 4 that the adhesion of the acrylic resin obtained without adding the above substances is not level 2, the time used for water washability is increased, and the hole position accuracy and hole wall roughness are reduced, indicating that starch modification, benzoyl chloride, N,N-methylenebisacrylamide and hexadecyldimethylallyl ammonium chloride play a significant role in improving the water washability and compatibility of acrylic resin coatings.
[0098] In addition, the pkHHR and THR of the acrylic resin film without the addition of 3,4-epoxy-1-butene and diethanolamine increased, and the water washability of the film was reduced without the addition of acrylamide and hydroxyethyl acrylate.
Claims
1. Preparation of key materials for flame-retardant, washable, moderately compatible water-based acrylic resin coatings, characterized in that: Prepare according to the following steps: The flame retardant, water-washable and moderately compatible water-based acrylic resin coating is solved, and the key materials are a carbonizing agent intermediate, a porous carbon layer modification and a starch modification; The preparation method of the carbon-forming agent intermediate is as follows: Add 6.1g of p-hydroxybenzaldehyde into a beaker, stir and dissolve with 100-150mL of ethanol, pour into a 250mL three-necked flask, stir at a speed of 250r / min, heat to 50-60°C, slowly drop 1.5-1.8g of ethylenediamine diluted with 10mL of ethanol into the three-necked flask through a constant pressure dropping funnel for 30min, continue to react for 1-2.5h, stop heating, cool to room temperature, filter to obtain a pale yellow crude carbon-forming intermediate, wash with ethanol 3 times, and vacuum dry at 60°C for 18-24h to obtain a pale yellow carbon-forming intermediate powder, which is a carbon-forming agent intermediate; The preparation method of the porous carbon layer modified material is: (1) Cutting vegetable tanned leather scraps into blocks with a length and width of 1 cm, placing them in a vacuum tube furnace, heating them at 400° C. for 3 to 4 hours under a nitrogen atmosphere for pre-carbonization, mixing the obtained carbonized product with KOH at a weight ratio of 1:3, then adding 300% of its weight of water to the mixture, stirring at 40 to 50° C. for 18 to 22 hours, then drying the product, and then carbonizing and keeping it warm at 500 to 600° C. for 1 to 2 hours under nitrogen protection, and finally drying it to obtain a porous carbon layer; (2) 0.5 g of porous carbon layer, 4.5-6.7 g of pyrrole, 100 mL of water, and 0.4-0.6 g of sodium p-toluenesulfonate were stirred at 50-60° C. for 2-4 h, the product was dried, and then 50 mL of DMF and 8.17-11.2 g of erythritol were added, the pH was adjusted to 7.5, and the reaction was stirred at 50-70° C. for 1-2 h. Then 27.4-36.4 g of phosphorus trichloride was added, and the reaction was carried out at 30-40° C. for 1-2 h. Then 12.5-15.3 g of myristic acid was added, and the reaction was carried out at 30-45° C. for 1-2 h. The product was dried to obtain a porous carbon layer modified product. The preparation method of the starch modified material comprises: adding 1-1.2 g of benzoyl chloride and 15 mL of benzene to 4 g of soluble starch, stirring and reacting at 30-40° C. for 30-40 min, rotary evaporating at 40-50° C., and drying to obtain a starch reactant; then adding 20 mL of 70° C. deionized water to the starch reactant, stirring for 30-40 min, adding 0.03-0.05 g of ammonium persulfate at 50-60° C. to obtain a pregelatinized soluble starch solution; then adding 5.8 g of acrylamide and 2.3 g of hexadecyl dimethyl allyl chloride to the starch reactant. Mix ammonium hydroxide and 2g of N,N-methylenebisacrylamide, add them into 10mL of deionized water to dissolve, then slowly pour the solution into the pre-gelatinized soluble starch solution, adjust the pH of the solution to 7.0 with 1mol / L NaOH, react for 15-30min, the mixed solution becomes a gel state, stir at 60-70℃ for 2-3h, then cut the gel into pieces with scissors, place it in an electric blast drying oven at 90℃ to react for 2-3h, finally take it out and dry it for 24h, crush it through an 18-mesh sieve to get the starch modification.
2. The flame retardant, washable, moderately compatible water-based acrylic resin coating key material preparation as claimed in claim 1, characterized in that: The preparation method of the flame retardant, water-washable, moderately compatible water-based acrylic resin coating is as follows: (1) Preparation of core layer emulsion: Add 600-800 g of water, 11-17 g of emulsifier A, and 24-41 g of methacrylic acid to a reaction container, mix and stir evenly, heat to 40-45° C., stir and react for 60 min, then add monomer A, 10.2-13.4 g of carbonizing agent intermediate, 18.3-21.6 g of DOPO, and 2.1-6.3 g of 3,4-epoxy-1-butene, and emulsify for 20-30 min; heat to 65° C., pass reflux water, heat to 80-90° C., dropwise add 10-12 g of initiator, dropwise add for 1-1.5 h, react for 1-2 h, then add 3.15-8.4 g of diethanolamine, adjust the pH to 8, and react at 80-90° C. for 1-2 h to obtain core layer emulsion; (2) To the entire core layer emulsion obtained in step (1), all monomers B and 8-12 g of initiator are added dropwise at the same time for 1 hour, and the mixture is stirred at 75-85° C. for 1.5 hours. Then, 4.6-5.5 g of porous carbon layer modifier, 4.1-4.3 g of DOPO, 1.2-2.4 g of 3,4-epoxy-1-butene, 2.1 g of initiator and 1.1-2.3 g of starch modifier are added, and the mixture is reacted at 60-70° C. for 1 hour. The mixture is cooled to 50° C., 14-20 g of emulsifier B is added, and the reaction time is 30 minutes. Ammonia water is added to adjust the pH value to 7-8 to obtain a flame-retardant, washable, and moderately compatible water-based acrylic resin coating. The monomer A is prepared by mixing 40-55g of ethyl acrylate, 28-48g of methyl methacrylate and 38-52g of hydroxyethyl acrylate; The monomer B is prepared by mixing 49-69 g of acrylamide, 12-54 g of methyl methacrylate and 55-92 g of hydroxyethyl acrylate.
3. The flame retardant, washable, moderately compatible water-based acrylic resin coating key material preparation as claimed in claim 2, characterized in that: The emulsifier A is prepared by mixing sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2:
1.
4. The flame retardant, washable, moderately compatible water-based acrylic resin coating key material preparation as claimed in claim 2, characterized in that: The initiator is any one of ammonium persulfate and potassium persulfate.
5. The flame retardant, washable, moderately compatible water-based acrylic resin coating key material preparation as claimed in claim 2, characterized in that: The emulsifier B is AEO-9.
Citation Information
Patent Citations
A manufacturing method to improve the accuracy of back drilling on PCB boards
CN103533761B
Gluing aluminum-based cover plate for PCB drilling and preparing method thereof
CN110281308A
Preparation method of flame-retardant core-shell type environmentally friendly waterborne resin coating
CN112322132B
Washable temporary decorative coating for soft PVC (polyvinyl chloride) as well as preparation method and application of washable temporary decorative coating
CN114921135A